Clinical profile of retinal vein occlusion in Hospital Universiti Sains Malaysia a 7 years review - Ibrahim, Khairul Anwar; Rosli, Abdul Hadi; Hassan, Mutasim; Embong, Zunaina (Universiti Sains Malaysia, 2020)
To review the clinical profile of retinal vein occlusion (RVO) in Hospital Universiti Sains Malaysia (USM) from 2011 until 2017. This was a retrospective single-centre case series. The medical records of the patients presented to Ophthalmology Clinic with RVO from 2011 to 2017 were reviewed. A total of 24 patients (26 eyes) with a diagnosis of RVO in Hospital USM were reviewed. There was 91.6 of our patients were aged more than 45 years old with predominantly affected male gender (58.3). Majority of the patients were Malays (87.5). Hypertension (70.8), hyperlipidemia (70.8) and diabetes mellitus (54.2) were the common systemic comorbidities in RVO patients. Majority of the patients (87.5) were non-smoker. Based on type of RVO, there were 38.5 central RVO, 26.9 branch RVO, 19.2 macular branch RVO, and 15.4 hemivein occlusion. RVO was bilateral in 2 patients (8.4). Based on fundus fluorescein angiography, 3 patients (11.5) showed ischaemic features. Reduce vision (91.6) was the main presenting symptoms of RVO while intraretinal haemorrhage (100) and macular oedema (96.2) were the most common ocular signs found in RVO. There were 16 eyes (61.5) have visual acuity equal or better than 6/60 at presentation. Patient who had visual acuity equal or better than 6/60 showed promising improvement in visual acuity post treatment. Elderly with multiple comorbidities complaining of worsening of vision should have high index suspicion of RVO. Presenting visual acuity is associated with final visual outcome